Supplementation with conjugated linoleic acid and body composition: a systematic review - Delpino, Felipe Mendes (2022)
The present study aimed to review the literature on publications that evaluated the association between the intake of conjugated linoleic acid (CLA) and body composition in humans. This is a systematic review of the Pubmed, Lilacs and Scielo databases, with no restrictions on the year of publication and language of the studies. Medical Subject Headings (MeSH) was used to locate the terms. This review followed the rules of the Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA). Five hundred and eighty-three studies were found, of which 28 were in the inclusion criteria and were included in the review. Thirteen studies found no type of association and 15 found some association between CLA and body composition in humans. There appears to be no difference between moderate and high doses in the results. The main result of this study is that CLA appears to work modestly on fat loss in overweight or obese people. However, further studies are needed to prove the long-term effectiveness and safety of CLA.